Effect of carbon-interaction on structure-photoactivity of Cu doped amorphous TiO2 catalysts for visible-light-oriented oxidative desulphurization of dibenzothiophene. (15th March 2018) - Hitam, C.N.C.; Jalil, A.A.; Triwahyono, S.; Rahman, A.F.A.; Hassan, N.S.; Khusnun, N.F.; Jamian, S.F.; Mamat, C.R.; Nabgan, W.; Ahmad, A.
Graphical abstract: Highlights: C was self-doped onto amorphous TiO2 via an electrochemical method. C replaced Ti or O atoms to form Ti–O–C and O–Ti–C bonds. Band gap narrowing was mainly responsible for enhanced photoactivity. Introduction of dopants extended the spectral response to the visible region. Photogenerated holes had a significant role in the reaction. Abstract: Amorphous TiO2 (AT) was successfully prepared via the sol-gel technique, using different titanium sources followed by incorporation of copper via the electrochemical method to give CuO/TiO2 (CAT) catalysts. The catalysts were characterized via XRD, N2 physisorption, FTIR, TEM, EDX, XPS, ESR and UV–Vis DRS. The results verified that the use of different titanium precursors have profound effect on the physicochemical properties of the AT catalysts. Further one-pot self-doping carbon from titanium precursor during the addition of copper could greatly enhanced the photocatalytic activity of CAT on the oxidative desulphurization of dibenzothiophene (DBT). 15 CATTBOT exhibited the best performance mainly due to the narrowest band gap and higher numbers of O–Ti–C and Ti–O–C bonds, as well as appropriate amount of Ti 3+ surface defects (TSD). These abovementioned properties offered good mobility of electron-hole pairs and/or trap the electrons for enhancement of photoactivity under irradiation of visible light. Kinetic studies showed that the photocatalytic oxidative desulphurization of DBT followed the pseudo-first order Langmuir-Hinshelwood model, where the adsorption was the controlling step. It is believed that these results could contribute to the synthesis of various supported catalysts for numerous applications specifically in removal of sulphur containing compounds in fuel oils.